2017
DOI: 10.1159/000478649
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Iterated Rippled Noise Periodicity in Cochlear Implant Users

Abstract: Pitch perception is more challenging for individuals with cochlear implants (CIs) than normal-hearing subjects because the signal processing by CIs is restricted. Processing and perceiving the periodicity of signals may contribute to pitch perception. Whether individuals with CIs can discern pitch within an iterated rippled noise (IRN) signal is still unclear. In a prospective controlled psychoacoustic study with 34 CI users and 15 normal-hearing control subjects, the difference limen between IRN signals with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Accordingly, the additional activity in the variable prosody condition should be confined to central and posterior portions of right STC, where slow spectro-temporal modulations elicit the strongest responses in normal hearing ( Boemio et al, 2005 , Poeppel, 2003 ). Previous EEG studies with CI users have shown a reduced mismatch negativity to pitch changes relative to normal hearing ( Kelly et al, 2005 , Sandmann et al, 2009 , Sandmann et al, 2010 ), a smaller N1 evoked by pitch onsets ( Wagner et al, 2017 ), and that auditory ERPs hardly differed in response to tones with different degrees of frequency modulation ( Sandmann et al, 2015 ). Yet, the distribution of cortical activity in CI-based pitch processing cannot be inferred from these results.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Accordingly, the additional activity in the variable prosody condition should be confined to central and posterior portions of right STC, where slow spectro-temporal modulations elicit the strongest responses in normal hearing ( Boemio et al, 2005 , Poeppel, 2003 ). Previous EEG studies with CI users have shown a reduced mismatch negativity to pitch changes relative to normal hearing ( Kelly et al, 2005 , Sandmann et al, 2009 , Sandmann et al, 2010 ), a smaller N1 evoked by pitch onsets ( Wagner et al, 2017 ), and that auditory ERPs hardly differed in response to tones with different degrees of frequency modulation ( Sandmann et al, 2015 ). Yet, the distribution of cortical activity in CI-based pitch processing cannot be inferred from these results.…”
Section: Introductionmentioning
confidence: 97%
“…More generally, both diminished haemodynamic cortical activity in auditory areas ( Coez et al, 2008 , Giraud et al, 2000 ) as well as smaller and delayed auditory ERPs ( Agrawal et al, 2013 , Kelly et al, 2005 , Sandmann et al, 2009 , Sandmann et al, 2015 , Viola et al, 2011 , Wagner et al, 2017 ) have been observed in CI users relative to NH controls using different types of auditory stimuli. These effects were shown to increase with the duration of deafness before implantation ( Green et al, 2005 , Kelly et al, 2005 , Sandmann et al, 2010 , Viola et al, 2011 ) and possible explanations for them include the lower number of activated neurons as well as a reduction of synchronised neural activity caused by the limited sensory input provided by CIs ( Agrawal et al, 2013 , Sandmann et al, 2009 ).…”
Section: Introductionmentioning
confidence: 97%
“…In the current study, in addition to traditional measures, we chose Iterated Rippled Noise (IRN) to create a pitch contour with adjustable salience alongside Amplitude Modulation (AM) stimuli in quiet and in modulated noise as temporally complex stimuli in assessing the processing of temporal attributes. IRN has been used in neurophysiological and behavioral studies in both human (Krishnan et al 2014(Krishnan et al , 2015Peter et al 2014;Thompson and Marozeau 2014;Wagner et al 2017) and animal models (Bendor and Wang 2005;Alsindi et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We specifically chose Iterated Rippled Noise (IRN) with pitch sweep alongside Amplitude Modulation (AM) stimuli in quiet and in modulated noise as temporally complex stimuli in assessing the processing of temporal attributes. IRN was used in neurophysiological and behavioral studies in both human (Krishnan et al, 2014(Krishnan et al, , 2015Peter et al, 2014;Wagner et al, 2017;Shearer et al, 2018) and animal models (Bendor and Wang, 2005;Alsindi et al, 2018), creating "pseudo-pitch" pitch contours with broadband carriers. IRN bypasses limitations posed by animal frequency range as well as permitting easily adjustable pitch intelligibility by altering the number of noise iterations and thus, the strength of temporal regularity and pitch salience (Patterson et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, in addition to traditional measures, we chose Iterated Rippled Noise (IRN) to create a pitch contour with adjustable salience alongside Amplitude Modulation (AM) stimuli in quiet and in modulated noise as temporally complex stimuli in assessing the processing of temporal attributes. IRN has been used in neurophysiological and behavioral studies in both human (Krishnan et al 2014, 2015; Peter et al 2014; Thompson and Marozeau 2014; Wagner et al 2017) and animal models (Bendor and Wang 2005; Alsindi et al 2018).…”
Section: Introductionmentioning
confidence: 99%